Management of the Local Water supply in the Municipality of Ouèssè in Bénin - SEWADE, Grégoire; BIAOU, GAUTHIER; ADJAKPA, TCHÉKPO THÉODORE; GUEDENON, Patient; HOUSSOU, CHRISTOPHE SÈGBÈ (My University, 2015)
The availability of drinking water for the vital needs of the current and future generations is one of the biggest challenges the humanity is faced with. This study listed the problems connected to the management of the hydraulic infrastructures in the municipality of Ouèssè in the context of decentralization meant to contribute to its local development. The methodology used is based on desk study, direct observa-tions, ground study, and processing and analysis of data. The qualitative and statistical data were collected by means of tools (question-naires and interview guide) as well as collection techniques within different target groups (Agent, Farmer, intellectuals, resource person etc.). The study concerned three (03) villages and the research enrolled two hundred and sixty one (261) investigated persons. The profes-sionalization of the hydraulic infrastructures in the context of decentralization ended with the community-based management in the munic-ipality of Ouessè. That approach which is well appreciated in drinking water supply also meets chalenges. So the Weaknesses and Threats are identified as the social unrest observed at the level of some opinion leaders and the worrying silence of municipal authorities facing with the indelicacy of certain managers or opinion leaders. These aspects were the object of suggestion for the improvement of the management of Millennium development goals.
Keywords: Ouessè; Drinking water; Hydraulic infrastructures; Management